(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Introduction: The baby-friendly hospital initiative is a global program launched by WHO and UNICEF in 1991 to encourage hospitals, mainly maternity wards to implement practices that protect, promote, and support breastfeeding. This study aimed to assess Knowledge and Practice regarding breastfeeding of BFHI among Nurses. Method: A cross-sectional analytical study design was used among nurses of Maternity, Children, Gynaecology, and Postpartum wards of Patan Hospital, from January 2019 to February 2020. Data on knowledge of baby-friendly hospital initiative and breastfeeding was collected by using a self-administered structured questionnaire and practice of breastfeeding by observation checklist. Descriptive (frequency, percentage, mean, standard deviation) and inferential (Chi-square, normality test, and Spearman’s rank correlation) statistics were used for data analysis with SPSS version 20. Result: The findings show that out of 100 nurses surveyed, more than half (58%) of the respondents had a good level of knowledge and less than one-fourth (23.8%) had a good level of practice of breastfeeding. There was no significant association between level of knowledge and baby-friendly hospital initiative in the nursing course (p=0.814), training on breastfeeding in hospital (p=0.069), or outside (p=0.944). There was a weak positive correlation between knowledge and practice of breastfeeding. Conclusion: Compared to knowledge on breastfeeding, the practice was quite low among the nurses.